Synthesis of an organoinsulin molecule that can be activated by antibody catalysis - Worrall, Dorothy S. (The National Academy of Sciences, 2001)
We have developed a methodology of prodrug delivery by using a modified insulin species whose biological activity potentially can be regulated in vivo. Native insulin was derivatized with aldol-terminated chemical modifications that can be selectively removed by the catalytic aldolase antibody 38C2 under physiologic conditions. The derivatized organoinsulin (insulin(D)) was defective with respect to receptor binding and stimulation of glucose transport. The affinity of insulin(D) for the insulin receptor was reduced by 90% in binding studies using intact cells. The ability of insulin(D) to stimulate glucose transport was reduced by 96% in 3T3-L1 adipocytes and by 55% in conscious rats. Incubation of insulin(D) with the catalytic aldolase antibody 38C2 cleaved all of the aldol-terminated modifications, restoring native insulin. Treatment of insulin(D) with 38C2 also restored insulin(D)'s receptor binding and glucose transport-stimulating activities in vitro, as well as its ability to lower glucose levels in animals in vivo. We propose that these results are the foundation for an in vivo regulated system of insulin activation using the prohormone insulin(D) and catalytic antibody 38C2 with potential therapeutic application.